Patients’ perspective on mental health specialist video consultations in primary care: qualitative preimplementation study of anticipated benefits and barriers - Bleyel, Caroline; Hoffmann, Mariell; Wensing, Michel; Hartmann, Mechthild; Friederich, Hans-Christoph; Haun, Markus W. (Journal of medical internet research, 2020)
Background: Due to limited access to specialist services, most patients with common mental disorders (depression or anxiety, or both) usually receive treatment in primary care. More recently, innovative technology-based care models (eg, video consultations) have been proposed to facilitate access to specialist services. Against this background, the PROVIDE (Improving Cross-Sectoral Collaboration Between Primary and Psychosocial Care: An Implementation Study on Video Consultations) project aims to improve the provision of psychosocial care through implementing video consultations integrated into routine primary care. - Objective: From the patients’ perspective, this qualitative preimplementation study explored (1) anticipated benefits from and (2) barriers to implementing mental health specialist video consultations embedded in primary care services and (3) prerequisites for interacting with therapists via video consultations. - Methods: Using a purposive (ie, stratified) sampling strategy, we recruited 13 patients from primary care practices and a tertiary care hospital (psychosomatic outpatient clinic) for one-off semistructured interviews. In a computer-assisted thematic analysis, we inductively (bottom-up) derived key themes concerning the practicability of mental health specialist video consultations. To validate our results, we discussed our findings with the interviewees as part of a systematic member checking. - Results: Overall, we derived 3 key themes and 10 subthemes. Participants identified specific benefits in 2 areas: the accessibility of mental health specialist care (shorter waiting times: 11/13, 85%; lower threshold for seeking specialist mental health care: 6/13, 46%; shorter travel distances: 3/13, 23%); and the environment in primary care (familiar travel modalities, premises, and employees: 5/13, 38%). The main barriers to the implementation of mental health video consultations from the patients’ perspective were the lack of face-to-face contact (13/13, 100%) and technical challenges (12/13, 92%). Notably, participants’ prerequisites for interacting with therapists (12/13, 92%) did not seem to differ much from those concerning face-to-face contacts. - Conclusions: Mental health service users mostly welcomed mental health specialist video consultations in primary care. Taking a pragmatic stance, service users, who are often frustrated about uncoordinated care, particularly valued the embedment of the consultations in the familiar environment of the primary care practice. With respect to interventional studies and implementation, our findings underscore the need to minimize technical disruptions during video consultations and to ensure optimal resemblance to face-to-face settings (eg, by training therapists in consistently reacting to nonverbal cues). - Trial Registration: German Clinical Trials Register DRKS00012487; https://tinyurl.com/uhg2one - [J Med Internet Res 2020;22(4):e17330]
Gesehen am 07.05.2020